2008
DOI: 10.1021/jp800944r
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Water on Cu2O and Al2O3 Thin Films

Abstract: The initial stages of water condensation, approximately 6 molecular layers, on two oxide surfaces, Cu 2 O and Al 2 O 3 , have been investigated using ambient pressure x-ray photoelectron spectroscopy at relative humidity values (RH) from 0 to > 90%. Water adsorbs first dissociatively on oxygen vacancies producing adsorbed hydroxyl groups in a stoichiometric reaction: O lattic + Vacancies + H 2 O = 2OH. The reaction is completed at ~ 1% RH and is followed by adsorption of molecular water. The thickness of the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
149
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(166 citation statements)
references
References 32 publications
15
149
2
Order By: Relevance
“…Similar studies have been conducted on copper oxide and aluminum oxide. These studies found that adsorbed water will react with lattice oxygen to form OH and that this reaction is completed by ~1% RH [44]. Increasing RH beyond this point results in an adsorbed water layer that reaches a monolayer near 15% RH and about 6 layers at 90% RH [44].…”
Section: Environmental Effect On Friction and Wear Of Metalsmentioning
confidence: 97%
“…Similar studies have been conducted on copper oxide and aluminum oxide. These studies found that adsorbed water will react with lattice oxygen to form OH and that this reaction is completed by ~1% RH [44]. Increasing RH beyond this point results in an adsorbed water layer that reaches a monolayer near 15% RH and about 6 layers at 90% RH [44].…”
Section: Environmental Effect On Friction and Wear Of Metalsmentioning
confidence: 97%
“…This is based on reports by other groups on the interaction of water vapor with the surfaces of various metal oxides including SiO 2 . 28,[32][33][34][35] In these studies, it was argued that the hydroxylation precedes the growth of a molecular water film, and the former starts at an RH of much lower than 1%. After the saturation of hydroxyl formation at a RH of around 1%, the adsorption of molecular water begins as a result of the attractive interaction between H 2 O molecules and hydroxyls.…”
Section: B Ap-xps Experimentsmentioning
confidence: 99%
“…It is known that OH is readily formed on surfaces in the presence of H 2 O pressure as low as 1 × 10 -7 torr. 19 The peak at 536.3 eV is due to the gas phase CO 2 . Interestingly, we found that in the presence of CO 2 the incident x-rays or the emitted photoelectrons induce the formation of carbonate species on the surface.…”
Section: Cu 2 O In Vacuum and In The Presence Of 01 Torr Comentioning
confidence: 99%